Pengaruh Latihan SAQ (Speed, Agility, And Quickness) terhadap Kecepatan Tendangan Dollyo Chagi pada Atlet Caraka Taekwondo Subang - Deden Budi Rosman; Alda Alvita Fortuna; Gempar Al-Hadist (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study is based on facts in the field regarding the speed of the dollyo chagi kick. The aim of this study was to determine the effect of SAQ (Speed, Agility, and Quickness) training on the speed of the dollyo chagi kick of Caraka Taekwondo Subang athletes. The method used in this research is Experimental with a One-Group Pretest-Posttest Design. The population in this study were 10 athletes from Caraka Taekwondo Subang aged 13-17 years. Sampling was done by using purposive sampling. The instrument used was a 10-second dollyo chagi kick speed test. Data analysis used the paired sample t-test. The results showed a significant increase in the speed of the dollyo chagi kick with a Sig. (2-tailed) value of 0.000 < 0.05. It can be concluded that SAQ training has a significant effect on increasing the speed of the dollyo chagi kick in Caraka Taekwondo Subang athletes.